LEFT-VENTRICULAR HYPERTROPHY AS A RISK FACTOR for ARRHYTHMIAS in HEMODIALYSIS-PATIENTS - Saragoca, Manoel A. [UNIFESP] (1991)
The contribution of left ventricular hypertrophy in determining ventricular arrhythmias (VAS) was studied in 81 chronic renal failure patients in chronic hemodialysis using two-dimensional echocardiographic and electrocardiogram Holter monitoring. the prevalence of LVH was 93% (96% in hypertensive and 87% in normotensive patients). the prevalence of VA was 48%. These arrhythmias were associated with increased cardiac mass, lack of potassium supplementation to the hemodialysis bath, and low K+ and PaO2 during dialysis. Severe forms of VA occurred in 19 of 78 patients, and the risk factors for this occurrence were (a) largely increased cardiac mass indices (exceeding in more than 40% the upper limit of normal for each sex) and (b) prolonged periods of time in hemodialysis treatment (34 +/- 5.5 vs. 17 +/- 2.7 months, p < 0.05). Changes in potassium or oxygen content of the blood were not significantly associated with the occurrence of severe forms of VA.